Comparative Effectiveness of Influenza Vaccines Among US Medicare Beneficiaries Ages 65 Years and Older During the 2019–2020 Season. (19th November 2020) - Izurieta, Hector S; Lu, Michael; Kelman, Jeffrey; Lu, Yun; Lindaas, Arnstein; Loc, Julie; Pratt, Douglas; Wei, Yuqin; Chillarige, Yoganand; Wernecke, Michael; MaCurdy, Thomas E; Forshee, Richard
Abstract: Background: Approximately 50 000 influenza-associated deaths occur annually in the United States, overwhelmingly among individuals aged ≥65 years. Although vaccination is the primary prevention tool, investigations have shown low vaccine effectiveness (VE) in recent years, particularly among the elderly. We analyzed the relative VE (RVE) of all influenza vaccines among Medicare beneficiaries aged ≥65 years to prevent influenza hospital encounters during the 2019–2020 season. Methods: Retrospective cohort study using Poisson regression and inverse probability of treatment weighting (IPTW). Exposures included egg-based high-dose trivalent (HD-IIV3), egg-based adjuvanted trivalent (aIIV3), egg-based standard dose (SD) quadrivalent (IIV4), cell-based SD quadrivalent (cIIV4), and recombinant quadrivalent (RIV4) influenza vaccines. Results: We studied 12.7 million vaccinated beneficiaries. Following IPTW, cohorts were well balanced for all covariates and health-seeking behavior indicators. In the adjusted analysis, RIV4 (RVE, 13.3%; 95% CI, 7.4–18.9%), aIIV3 (RVE, 8.2%; 95% CI, 4.2–12.0%), and HD-IIV3 (RVE, 6.8%; 95% CI, 3.3–10.1%) were significantly more effective in preventing hospital encounters than the reference egg-based SD IIV4, while cIIV4 was not significantly more effective than IIV4 (RVE, 2.8%; 95% CI, −2.8%, 8.2%). Our results were consistent across all analyses. Conclusions: In this influenza B-Victoria and A(H1N1)–dominated season, RIV4 was moderately more effective than other vaccines, while HD-IIV3 and aIIV3 were more effective than the IIV4 vaccines, highlighting the contributions of antigen amount and adjuvant use to VE. Egg adaptation likely did not substantially affect our RVE evaluation. Our findings, specific to the 2019–2020 season, should be evaluated in other studies using virological case confirmation. Abstract : The recombinant (RIV4), adjuvanted standard dose (SD) egg-based trivalent (aIIV3), and the high-dose egg-based trivalent (HD-IIV3) vaccines had higher effectiveness than the SD egg-based quadrivalent vaccines (IIV4), highlighting the contributions of antigen amount and adjuvant use to influenza vaccine effectiveness.